Carbohydrate-mediated antigenic cross-reactivity between Schistosoma mansoni antigens and environmental allergens - Gai, Fatou (2020)
There has been an increase in allergic diseases such as asthma, which triggers an IgE allergic reaction, in countries with advanced health systems. However, in helminth-endemic countries, an inverse correlation between infection with parasitic helminths including schistosomes and allergic sensitisation has been observed. This has led authors to formulate the so-called hygiene hypothesis. Previous studies have shown that rabbit IgG antibodies against Schistosoma mansoni soluble egg antigens (SmSEA) cross-reacted with various allergens such as peanut, rubber latex and grass and tree pollens. Here we describe antigenic molecules that cross-react with rabbit anti-S. mansoni IgG antibodies in extracts of the Australian cockroach (ACR) Periplaneta australasiae and the house dust mite (HDM) Dermatophagoides farinae. Our investigation was carried out using sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS-PAGE) and western immunoblotting using rabbit antisera raised against S. mansoni antigen. The purified material was subjected to Tandem mass spectrometry to identify S. mansoni antigen that is cross-reactive with molecules in an extract of the different allergens. We found the cross-reactive allergens as Der f 15 in HDM and two homologues of the Periplaneta americana cockroach allergen Cr-PI/Per a 3 in ACR. Acid elution of anti-SmSEA antibodies cross-reactive with the allergens reacted with the major egg antigens of S. mansoni namely IPSE-alpha 1, Kappa-5 and Omega-1. Moreover, rabbit anti-schistosome IgG antibodies eluted from HDM reacted with a variety of plant extracts. Treatment with sodium meta periodate ablated most of the cross-reactivity of the antigen suggesting that it might be due to cross-reactive carbohydrate determinants (CCDs). In this work, we have also used the humanized Rat Basophilic Leukemia RS-ATL8 reporter system which is used to detect allergen-specific IgE in human serum. The reason for using such a system was to investigate whether anti-schistosome IgG antibodies that are cross-reactive with an allergen – D. farinae - can act as ‘blocking antibodies. We found that the two different donor serum samples used were able to sensitise the reporter cells upon challenge with anti-human IgE, but when challenged with the mite allergen there was only a very low response. This could mean that the molecule Der f 15, which is a minor HDM allergen, might not be the target of an allergen-specific IgE response in these two donors. Furthermore, we developed an in vitro system to study if recombinant IgG can block IgE mediated activation using Phl p 7 a well-known characterised allergen. This was carried out by expressing IgE and IgG protein in mammalian HEK 293 cells, the expressed IgG protein was purified using Affinity Chromatography ÄKTAstart system. Our data show that the two proteins were successfully expressed, and the IgG protein was also purified successfully. In conclusion, chapter 3 and 4 findings could provide a useful application for improved allergen-specific immunotherapy. Furthermore, we could use our reporter system to demonstrate that recombinant IgG antibodies can block the interaction of anti-Phl p 7 IgE antibody with Phl p 7 allergen, thereby blocking allergen-mediated crosslinking of IgE receptors in chapter 5.